PENYEDIAAN ENERGI LISTRIK DARURAT DAN PENANGANAN KRISIS AIR BERSIH UNTUK MASYARAKAT TERDAMPAK BANJIR BANDANG DI KABUPATEN PESISIR SELATAN - Dendi Adi Saputra M; Devi Chandra; Eka Satria; Adjar Pratoto; Febrin Anas Ismail; Fauzan Fauzan; Abdul Hakam; Bambang Istijono (LPPM Universitas Andalas, 2025)
The purpose of this community service activity is to assist the recovery of social activities and address the crisis of electricity and clean water following the flash floods in Pesisir Selatan Regency, particularly in Kampung Langgai and Barung-Barung Balantai Health Center, which were the most severely affected areas. The methods employed included conducting a needs assessment survey of the affected communities, procuring and installing a 5.5 kW generator set at Nurul Wahidah Mosque as a social center, distributing ten solar-powered lamps to residents’ homes, and rehabilitating the clean water system at the health center by replacing the water pump and installing new piping networks from the ring well and Pamsimas sources. Additionally, training was provided on the operation and maintenance of electrical equipment, along with socialization on the importance of clean water to prevent post-flood diseases. The results demonstrated a significant improvement in access to electricity and clean water in the affected areas. The mosque resumed its function as a center for social activities, homes and roads received adequate lighting, and health services at the health center became fully operational again. The conclusion of this activity is that appropriate technology-based interventions, such as the provision of generator sets, solar lamps, and water filtration system repairs, are effective in supporting post-disaster recovery and enhancing community resilience. The sustainability of the program can be strengthened through regular training and cross-sector collaboration to build resilient infrastructure in disaster-prone areas.